Data analysis of resident engagement and sentiments in social media enables better household waste segregation and recycling. (15th October 2021) - Jiang, Peng; Zhou, Jieyu; Fan, Yee Van; Klemeš, Jiří Jaromír; Zheng, Meimei; Varbanov, Petar Sabev
Abstract: Waste segregation, recycling and reduction have been prioritised in the Circular Economy transition of household waste management to reduce environmental impacts. With digitalisation and innovation developments in waste management, residents become more active on waste management-related social media platforms. However, there is still needed a tangible analysis of resident engagement (e.g. user comments and interactions) and related sentiment changes on such platforms to enhance waste management and ease the environmental burden at source. This study develops an integrated solution to analyse resident engagement by leveraging statistical analysis and text-mining methods. Four interrelated components are incorporated in the solution: population behaviour quantification, sentiment analysis and dynamics, popular concerns and probability distribution fitting, and rule-based managerial insight identification. The novel solution is applied to a real-world case study on a subscription account related to waste management in Shanghai. This research produces several major observations based on the studied case: (i) The resident engagement Monday-to-Thursday was more active than Friday-to-Sunday. (ii) Compared to 2018, the resident engagement by commenting on online posts was elevated by 107.1% in 2019 when Shanghai introduced a new management policy. Meanwhile, the yearly resource-type waste collection was increased by 114.5% in 2019. (iii) It took approximately one year to recover positive sentiments in user comments after introducing the policy. However, the comments with negative sentiments assisted in improving waste management. (iv) The best-fitted negative binomial distribution of the number of votes for user comments could guarantee the managerial insight identification from the minority of comments with popular concerns. Highlights: This study investigates resident engagement in waste management-related social media. User sentiment dynamics in social media reveal the impacts of waste management policies. Data analytics and observations improve waste recycling and ease environmental impact. Resident engagement in Shanghai Green Account in 2019 was increased by 107.1% from 2018. Average waste collection of resource-type waste in 2019 was elevated by 114.5% from 2018.